Analysis of the Influence of Self-Training and Entrepreneur Education on Readiness Entrepreneurship (Case Study in Stmb Multismart Students Medan) - Mario Andriaskiton; Angel Wang (Enrichment : Journal of Management, 2022)
The implementation of this study aims to analyze the effect of self-training and entrepreneurship education on entrepreneurial readiness in STMB MULTISMART Medan students. The research method uses descriptive quantitative. Methods of data collection using a questionnaire that will be measured using a Likert scale. The data analysis technique used is multiple linear regression analysis, partial testing, simultaneous testing and testing the coefficient of determination. The results of this study indicate that partially or simultaneously the variables of self-training and entrepreneurship education have a significant influence on entrepreneurial readiness in STMB MULTISMART Medan students.